2005
DOI: 10.1093/cercor/bhi063
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Incentives Enhance Processing in Brain Regions Mediating Top-down Control of Attention

Abstract: To evaluate the effect of an abstract motivational incentive on top-down mechanisms of visual spatial attention, 10 subjects engaged in a target detection task and responded to targets preceded by spatially valid (predictive), invalid (misleading) or neutral central cues under three different incentive conditions: win money (WIN), lose money (LOSE), and neutral (neither gain nor lose). Activation in the posterior cingulate cortex was correlated with visual spatial expectancy, defined as the degree to which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
179
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(211 citation statements)
references
References 57 publications
30
179
2
Order By: Relevance
“…The area under the characteristic curve (AUC) represents the strength of the predictive signal. ment in cue utilization is consistent with previous suggestions that it acts as an interface between high-level reward signals and the attentional system (41). Sensory-motor cortices (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The area under the characteristic curve (AUC) represents the strength of the predictive signal. ment in cue utilization is consistent with previous suggestions that it acts as an interface between high-level reward signals and the attentional system (41). Sensory-motor cortices (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our prior work (15), we observed that changing the incentive value of trials had a striking influence on both behavioral performance and neural activity in lateral PFC. Similar findings have also been observed in prior studies examining working memory (30,31) and attentional tasks (32). Our findings indicated that reward-and penalty-based incentives had very distinct effects on behavior and brain activity during the AX-CPT.…”
Section: Discussionsupporting
confidence: 90%
“…Such scarce evidence contrasts with the psychophysiological studies showing enhanced P300 when processing reward cues and outcomes (Parvaz et al 2012;van Lankveld and Smulders 2008;Yeung and Sanfey 2004), and with functional connectivity studies showing increased coupling between the parietal and striatal areas in the presence of reward cues (Padmala and Pessoa 2011). Furthermore, fMRI studies using attentional paradigms have revealed the greater involvement of the fronto-parietal areas when processing rewarding stimuli that compete with other stimuli (Small et al 2005;Locke and Braver 2008;Mohanty et al 2008;Engelmann et al 2009;Ivanov et al 2011). …”
Section: Introductionmentioning
confidence: 95%